(untitled) (Damascus University Journal of agriculture sciences, 2021)
This research was carried out to determine the genetic diversity of ten of local brown chicken (Br) and compared to five laying hen (HN) Spanish hybrid, The ISSR technique was carried out using (11) Primer of ISSR markers, they all gave PCR products, the percentage Percent Agreement Values of polymorphism was 96.26%. The highest Value of percentage agreement value in HN group was 0.95 between HN2, HN3, and the lowest value was 0.84 between HN4 and (HN2, HN3). The members of this group are relatively homogeneous and their degree of genetic relationship is high, while within the domestic brown group, the highest (PAV) value was 0.93 between Br6, Br9, the lowest value was 0.48 between Br4, Br9. Thus, local brown birds were relatively heterogeneous due to the random mating that resulted from breeding them in the other groups. The dendrogram was divided into two main clusters: • The first cluster included all the HN genotypes and it was divided into two subclusters, the first one included two genotype HN4, HN5. The second one included three genotype HN2, HN3which are closest to each other. The dendrogram thus showed the high relationship within this group. • The second cluster included all brown domestic birds, and itself was divided into two subclusters, the first subcluster included four males regardless of the area. The second subcluster included all females regardless of the area, plus the male Br5.